A point mutation in the nuclease domain of MLH3 eliminates repeat expansions in a mouse stem cell model of the Fragile X-related disorders - Hayward, Bruce E (Nucleic Acids Res, 2020)
The Fragile X-related disorders (FXDs) are Repeat Expansion Diseases, genetic disorders that result from the expansion of a disease-specific microsatellite. In those Repeat Expansion Disease models where it has been examined, expansion is dependent on functional mismatch repair (MMR) factors, including MutLγ, a heterodimer of MLH1/MLH3, one of the three MutL complexes found in mammals and a minor player in MMR. In contrast, MutLα, a much more abundant MutL complex that is the major contributor to MMR, is either not required for expansion or plays a limited role in expansion in many model systems. How MutLγ acts to generate expansions is unclear given its normal role in protecting against microsatellite instability and while MLH3 does have an associated endonuclease activity, whether that contributes to repeat expansion is uncertain. We show here, using a gene-editing approach, that a point mutation that eliminates the endonuclease activity of MLH3 eliminates expansions in an FXD mouse embryonic stem cell model. This restricts the number of possible models for repeat expansion and supports the idea that MutLγ may be a useful druggable target to reduce somatic expansion in those disorders where it contributes to disease pathology.